Langerhans cell histiocytosis of liver - Samudrala, Swapna; Sekaran, Anuradha; Patodiya, Bharat; Duvuru, Nageshwar Reddy (International Journal of Research in Medical Sciences, 2020)
Langerhans cell histiocytosis (LCH) is a rare disorder of unknown etiology caused by proliferation of Langerhans cells. It can involve single organ system to multi organ systems and clinical presentation is variable depending on the organ involved and have different prognosis. LCH is common in children when compared to adults. Hepatic involvement in adults is relatively rare. Liver involvement has considerable impact on survival rates. Histopathology and immunohistochemistry provide the definitive diagnosis. Authors report a case of Langerhans cell histiocytosis in a young adult with hepatic involvement.